Effects of calcination temperature on microstructure and superconducting properties of Y123 ceramic prepared using thermal treatment method - Dihom, Mustafa Mousa; Shaari, Abdul Halim; Baqiah, Hussein; Al-Hada, Naif Mohammed; Chen, Soo Kien; Azis, Raba’ah Syahidah; Kechik, Mohd Mustafa Awang; Abd. Shukor, Roslan (Trans Tech Publications, 2017)
Thermal treatment method was employed to produce YBa2Cu3Ox superconductor ceramic. The effects of calcination temperature at 850 °C, set A, and 910 °C, set B, for 24 h followed by sintering at 930, 950 and 980 °C, were investigate using X-ray diffraction (XRD), scanning electron microscope (SEM) and four point probe measurement. The orthorhombic structure appears after calcination at 850 and 910 °C beside small amount of impurity phase such as Y2BaCuO5 (Y211). The samples exhibited metallic behaviour and the critical temperature, TC(R=0), increases with increasing sintering temperature. The TC(R=0) of samples calcined at 910 °C is higher than that of sample calcined at 850 °C. The highest TC(R=0), 87 K, was found for sample sintered at 980 °C of set B. An increase in grain size and homogeneity was observed as the sintering temperature increases. The set B sample sintered at 980 °C showed compact grains, which could result in the highest Tc (R=0).